2003
DOI: 10.1148/radiol.2282020651
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Mapping in Patients with Breast Carcinoma: Reproducibility of Lymphoscintigraphic Results

Abstract: Results of lymphoscintigraphy for lymphatic mapping in breast cancer are highly reproducible for assessment of the number of sentinel nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…In three patients, SLN was not detected on 30-min image, and it could not be detected at all even on the delayed images either (up to 180 min). Limited studies also showed that sensitivity of imaging is not significantly different in early and delayed images and almost all of the SLNs are visible on the early images [14][15][16]26]. The type of the radiotracer as well as the optimal time of imaging is largely determined by operating room scheduling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In three patients, SLN was not detected on 30-min image, and it could not be detected at all even on the delayed images either (up to 180 min). Limited studies also showed that sensitivity of imaging is not significantly different in early and delayed images and almost all of the SLNs are visible on the early images [14][15][16]26]. The type of the radiotracer as well as the optimal time of imaging is largely determined by operating room scheduling.…”
Section: Discussionmentioning
confidence: 99%
“…To date, very limited studies evaluated the need for delayed imaging and the difference between early and delayed image sets [14][15][16]. The value of continuing the imaging for a prolonged period of time, especially for the patients in which SLN was not detected on the early images and the question of how long shall we continue imaging in this condition, has not been addressed enough in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The deep injection techniques have been studied best [19]. The reproducibility of lymphoscintigraphy with deep tracer administration was shown to be 100% and this has not been studied using the superficial approach to our knowledge [20]. It will be hard to match the 100% score in view of the mere 85-88% reproducibility that was found in two melanoma studies using the intradermal injection technique [21,22].…”
mentioning
confidence: 99%
“…The technique can be trusted. Lymphoscintigraphy after intratumoral tracer administration is 100% reproducible [14]. We found in the literature a mere 11 recurrences in axillae from which a tumor-free sentinel node had been removed without complimentary axillary clearance in over 2,500 patients.…”
mentioning
confidence: 78%